2015
DOI: 10.1371/journal.pone.0123253
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Native Genetic Background in Admixed Populations Using Haplotypes, Phenotypes, and Pedigree Information – Using Cika Cattle as a Case Breed

Abstract: The aim of this study was to obtain unbiased estimates of the diversity parameters, the population history, and the degree of admixture in Cika cattle which represents the local admixed breeds at risk of extinction undergoing challenging conservation programs. Genetic analyses were performed on the genome-wide Single Nucleotide Polymorphism (SNP) Illumina Bovine SNP50 array data of 76 Cika animals and 531 animals from 14 reference populations. To obtain unbiased estimates we used short haplotypes spanning four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…The here designed and applied composite test combines six metrics that each provide distinct information components about past admixture events and offers an objective, statistically valid and powerful tool for the detection of admixed outliers. The composite statistic (Filzmoser et al., ) as well as the six single metrics rely on well‐established, broadly applied methods (UAR, Yang et al., ; Nearest Neighbour Graph, Steinig et al., ; and spA, Simčič et al., and this study) and were additionally confirmed by their consistency with historical records of local strains ().…”
Section: Discussionsupporting
confidence: 60%
See 4 more Smart Citations
“…The here designed and applied composite test combines six metrics that each provide distinct information components about past admixture events and offers an objective, statistically valid and powerful tool for the detection of admixed outliers. The composite statistic (Filzmoser et al., ) as well as the six single metrics rely on well‐established, broadly applied methods (UAR, Yang et al., ; Nearest Neighbour Graph, Steinig et al., ; and spA, Simčič et al., and this study) and were additionally confirmed by their consistency with historical records of local strains ().…”
Section: Discussionsupporting
confidence: 60%
“…The here implemented methods and the use of multi‐allelic markers have the potential to reduce the ascertainment bias of the SNP array (Auton et al., ; Boyko et al., ; Lohmueller, Bustamante, & Clark, ; Simčič et al., ). Furthermore, they allowed us to demonstrate how to benefit from the allelic diversity of multi‐allelic markers as better indicators of future adaptation value (Caballero & Rodriguez‐Ramilo, ; Vilas et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations